How does the feeding behaviour of the common forest toad Rhinella henseli (Anura: Bufonidae) vary in space and time? Trophic ecology, chemical and antimicrobial activity. Supplementary Materials. Issue 2 (2022) - Huning, Douglas da Silva; Tonial, Fabiana; Oliveira, Mateus; Zanella, Noeli; Brandalise, Júlia de Moraes; Guerra, Kielli
No abstract available